ANALISIS KUANTITATIF KELENGKAPAN PENGISIAN RESUME MEDIS DI RUMKITAL DR. RAMELAN SURABAYA - Nofitalia Sawondari; Gamasiano Alfiansyah; Indah Muflihatin (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2021)
The medical resume form is a summarize of all the patient's treatment that is conducted by healthcareworkers and signed by a doctor. The filling completeness of the medical resume at RUMKITAL Dr.Ramelan Surabaya only reached 82.5%. The purpose of this research was to analyze e the completenessof medical resumes in RUMKITAL Dr. Ramelan Surabaya. This research was qualitative descriptive. Thedata collection used observation. The sample of this research as many as 20 medical resume forms inFebruary of 2020. The research results indicated the highest percentage of patient identification reviewincompleteness is 45% which is the inpatient’s rank or class item. The highest percentage ofincompleteness on important report's review is 55% which is the inpatient’s duration item. The highestpercentages of incompleteness on authentication are the patient's date item, the filling time, the patient’sor family’s name, also the patient’s or family’s signature. The highest percentage of incompleteness oncorrect documentation review is 20% which is the plain and legible registration. In conclusion, the highestincompleteness is in the identification review and the correct documentation. The research suggestion is tocreate the SOP of medical resume, the SPO socialization, and to sign a commitment about theconsistency of filling medical resumes.